Research on the dam foundation pit hydrogeological problems in Dadu river deep overburden layer area. (November 2019) - Zhang, Shishu; Kang, Xiaobing; Xu, Mo; Huang, Runtai; Hu, Jinshan; Li, Qiang; Ruan, Congyan
Abstract: Western Sichuan is located in the two and three steps of transition zone of our country on the terrain, in the area of Dadu River valley was "V" type, the valley is widely distributed deep overburden layer. The existence of deep overburden layer not only greatly increases the difficulty of hydropower development in the southwest region, but also gives birth to a series of new scientific problems. This paper analyze the basic feature and formation of deep overburden layer in the Dadu River, and then discuss the may encounter hydrogeological problems with the pit water gushing, piping and flow sand.